Galectin-1 in Cardiovascular Pathogenesis: Unraveling Dual Roles and Mechanistic Insights in Emerging Research - Po-Yuan Chen; Chun-Yao Cheng; Chun-Chao Chen; Huan-Yuan Chen; Ju-Chi Liu; Wen-Rui Hao; Tzu-Hurng Cheng; Jin-Jer Chen (Medicina, 2025)
Galectin-1 (Gal-1), a β-galactoside-binding lectin, plays a complex role in cardiovascular diseases (CVDs), exerting both protective and pathological effects depending on the context. This review synthesizes findings from the past decade to explore Gal-1’s involvement in key aspects of CVD pathogenesis, including vascular homeostasis, inflammation regulation, atherosclerosis progression, myocardial remodeling, and heart failure. While Gal-1 supports endothelial integrity and immune modulation, its dysregulation contributes to disease progression through pro-inflammatory signaling, fibrosis, and adverse cardiac remodeling. Emerging evidence suggests that Gal-1 holds potential as both a biomarker for risk assessment and a therapeutic target. However, critical knowledge gaps remain, particularly regarding its context-dependent effects, the limited scope of clinical trials, and unresolved mechanistic insights. Addressing these challenges will be essential to fully harness Gal-1’s therapeutic potential in cardiovascular medicine, guiding future research efforts toward precision interventions and clinical applications.